Leadership Roles For Improving Employee Productivity at Digital Start-Up Company - Ahmad Azmy; Agung Priyono (Jurnal Manajemen Bisnis, 2022)
Research aims: This study analyzes the role of leadership in improving employee productivity. The object of research was carried out at a start-up company engaged in the digital career development platform.Design/Methodology/Approach: The process of collecting data by conducting virtual interviews to gather information according to the research topic. Structured interviews were used in this study with the aim of obtaining systematic and specific information.Research findings: The results showed that the role of leadership is vital in increasing employee productivity. Theoretical contribution/ Originality: The six components that show the role of leadership in employee productivity include clarity of leadership functions, accuracy of competency-based employee placement, consistency of training programs, effectiveness of organizational strategy implementation, clarity of job description directions to employees, and a fair reward system based on contributions.Practitioner/Policy implication: This research has leadership implications for employee productivity. Leadership is very important in maintaining long-term business sustainability.Research limitation/Implication: This study is only limited to discussing the role of leadership to increase employee productivity accompanied by human resource strategies.